Modeling of physical and chemical equilibrium for the direct synthesis of dimethyl carbonate at high pressure conditions - B. A. V. Santos (2012)
The physical and chemical equilibrium for direct synthesis of dimethyl carbonate is studied using the Soave-Redlich-Kwong equation of state coupled with five different mixing rules: one fluid van der Walls (1PVDW), modified first order Huron-Vidal (mHV1), modified second order Huron-Vidal (mHV2), linear combination of Vidal and Michelsen (LCVM), and Wong-Sandler (WS). The models parameters were adjusted from experimental vapour-liquid equilibrium data, from the literature, for the relevant binary systems. The mHV2 mixing rule showed to be the best model to predict phase equilibrium for this system. Then, the DMC equilibrium yield was modeled based on the SRK/mHV2 model. The Gibbs free energy of formation, for DMC, was adjusted from our experimental reaction equilibrium data in order to predict the equilibrium constant.